Thermal physical properties and dephosphorisation kinetics of rare earth oxides containing slags. (26th November 2019) - Xi, Xiaojun; Yang, Shufeng; Lai, Chaobin; Li, Jingshe; Wang, Feng
ABSTRACT: The melting properties and viscosity of CaO–SiO2 –MnO–La2 O3 –CeO2 slags, with mass ratios of 0.97 and 1.05 between CaO and SiO2, were measured using the hot stage microscopy method and rotating cylinder method, respectively. In addition, the dephosphorisation kinetics of rare earth (RE) oxides containing slags was studied. For increasing mass contents of the RE oxides, La2 O3 and CeO2 (0, 3, 6, 9, and 12 wt.%), in the slag, the melting temperature initially decreases and then increases. Minimum values appeared for mass contents of 6 wt.%. RE oxide concentrations below 9 wt.% are beneficial to the decrease in viscosity, which increases significantly with the mass fraction of RE oxides in molten slags with a basicity of 1.05. In slags with a basicity of 0.97, the RE oxides favour the decrease in viscosity, which does not change noticeably as their mass fraction is increased above 6 wt.%. Finally, it was found that the rate-limiting step of the dephosphorisation process is the diffusion of phosphorus.